2016
DOI: 10.1177/1088767916634405
|View full text |Cite
|
Sign up to set email alerts
|

The Homicide Drop in Recife, Brazil

Abstract: Studies in crime concentrations have focused primarily on North America with a rather restrictive set of crime types. In this article, we analyze the crime concentrations and spatial patterns of homicide in Recife, Brazil. Brazil’s homicide rates have remained stable but at high levels, approximately 30 homicides per 100,000. Some places have experienced notable decreases in homicide: In Recife, the capital of Pernambuco, there has been a drop in the homicide rate of 46.67%, 2000 to 2012. We analyzed the decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Their sensitivity analysis suggested significant variations within larger spatial units. In the study of homicides in Recife (Brasil), Pereira, Mota, and Andresen (2016) partly declined spatial patterns' stability but found that crime was highly concentrated in the study area. In a longitudinal study on the stability of residential burglaries in Antwerp (Belgium), Vandeviver and Steenbeek (2017) indicate a moderate to a high degree of spatial stability over time.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Their sensitivity analysis suggested significant variations within larger spatial units. In the study of homicides in Recife (Brasil), Pereira, Mota, and Andresen (2016) partly declined spatial patterns' stability but found that crime was highly concentrated in the study area. In a longitudinal study on the stability of residential burglaries in Antwerp (Belgium), Vandeviver and Steenbeek (2017) indicate a moderate to a high degree of spatial stability over time.…”
Section: Introductionmentioning
confidence: 89%
“…Using a spatial point pattern test (SPPT), spatial stability of crime was analysed worldwide among various crimes. For example, in homicide analysis in Recife (Brasil), both global (analysis with all the areal units) and robust (sensitivity analysis with only non-zero event units) S values were found to be significant (Pereira et al, 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The complexity of decision-making in public security has been increasing, which is natural concerning the various aspects that influence decisions in this area, ranging among political, economic and socio-cultural issues, among others. In a 30 year-period (from 1980 to 2010), more than 1 million homicides were registered in Brazil (PEREIRA et al, 2016). As stated by the authors (PEREIRA et al, 2016), this number is astonishing for a country that was not experiencing any ethnic, religious and/or territorial conflicts.…”
Section: Introductionmentioning
confidence: 93%
“…In a 30 year-period (from 1980 to 2010), more than 1 million homicides were registered in Brazil (PEREIRA et al, 2016). As stated by the authors (PEREIRA et al, 2016), this number is astonishing for a country that was not experiencing any ethnic, religious and/or territorial conflicts. In addition, this is a scenario that has been getting worse and presents a certain urgency with regard to dedication to interventions that may reduce these numbers.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation